Closing the Yield Gap of Sugar Beet in the Netherlands—A Joint Effort - Hanse, Bram; Tijink, Frans G. J.; Maassen, Jurgen; van Swaaij, Noud (Frontiers in Plant Science, 2018)
The reform of the European Union’s sugar regime caused potential decreasing beet prices Therefore, the Speeding Up Sugar Yield (SUSY) project was initiated. At the start, a 3 x 15 target was formulated: in 2015 the national average sugar yield in the Netherlands equals 15 t/ha (60% of the sugar beet potential) and the total variable costs 15 euro/t sugar beet, aspiring a saving on total variable costs and a strong increase in sugar yield. Based on their average sugar yield in 2000-2004, 26 pairs of ‘type top’ (high yielding) and ‘type average’ (average yielding) growers were selected from all sugar beet growing regions in the Netherlands. On the fields of those farmers, all measures of sugar beet cultivation were investigated, including cost calculation and recording phytopathological, agronomical and soil characteristics in 2006 and 2007. Although there was no significant difference in total variable costs, he ‘type top’ growers yielded significantly 20% more sugar in each year compared to the ‘type average’ growers. Therefore, the most profitable strategy for the growers is maximising sugar yield and optimising costs. The difference in sugar yield between growers could be explained by pests and diseases (50%), weed control (30%), soil structure (25%) and sowing date (14%), all interacting with each other. The SUSY-project revealed the effect of the grower’s management on sugar yield. As a follow up for the SUSY-project, a growers’ guide ‘Suikerbietsignalen’ was published, Best Practise study groups of growers were formed and trainings and workshops were given and field days organised. Further, the benchmarking and feedback on the crop management recordings and the extension on variety choice, sowing performance, foliar fungi control and harvest losses were intensified. On the research part, a resistance breaking strain of the Beet Necrotic Yellow Vein Virus (BNYVV) and a new foliar fungus, Stemphylium beticola, were identified and options for control were tested, and implemented in growers practices. The joint efforts of sugar industry, sugar beet research and growers resulted in a raise in sugar yield form 10.6 t/ha in 2002-2006 to 13.8 t/ha in 2012-2016.